Labour and Product Market Reforms : A Case for Policy Complementarity - Donatella Gatti; Bruno Amable (Institute for the Study of Labor (IZA), 2004)
This paper is a contribution to the debate on policy complementarity in relation to deregulation in the product and labour markets. We develop a model of dynamic efficiency wages and monopolistic competition. Whereas most of the literature points toward the gains associated to an increase in product market competition coupled with an increased flexibility of the labour market, we show that even when more product market competition is the policy recommendation, it should be accompanied by an increase in job security.
Keywords: 330; policy complementarity; job protection legislation; efficiency wage; imperfect competition; Deregulierung; Wettbewerb; Arbeitsmarktflexibilisierung; Kündigungsschutz; Monopolistischer Wettbewerb; Effizienzlohn; Wohlfahrtseffekt; Theorie